Find (f+g)(x) for the following two functions:

f(x)=2x+1

g(x)=5x-3

(a) (f+g)(x)= x

(b) (f+g)(x)= 3x-2

(c) (f+g)(x)= 7x-2

(f+g)(x) = f(x) + g(x)

(f+g)(x) = 2x + 1 + 5x - 3

(f+g)(x) = 7x - 2

A.

(f+g)(x) = x

7x-2 = x

6x = 2

x = 1/3

B.

(f+g)(x)= 3x-2

7x-2 = 3x-2

4x = 0

x = 0

C.

(f+g)(x)= 7x-2

7x-2 = 7x-2

0 = 0

D.

(f+g)(x)= 8x-3

7x-2 = 8x-3

1 = x

x = 1

hello, are you saying the answer is

and if so than what are the letter a b c and d for ?? or are those part of the answer as well?

oh i mean the answer is C

i think we need to simplify..

if this option question the answer is c

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up